OBLIGATION TO MAKE ADDITIONAL PAYMENTS IN A LIMITED LIABILITY COMPANY - Marjanski, Vladimir (Zbornik radova Pravnog fakulteta u Novom Sadu, 2022)
The obligation to make additional payments is the obligation of the members of a limited liability company to pay the company the amounts of money that finance the company without increasing the share capital and which can be returned to them when the legal conditions are met. The subject of analysis in this paper are legal solutions related to additional payments in Serbian law and the law of individual countries (the law of Croatia, Austria and Germany). The mentioned comparative legal solutions will be processed especially only in those places where the legal rules in connection with additional payments differ significantly in relation to Serbian law. In particular, the subject of the analysis are the following issues: 1. Establishment of the legal basis and determination and formulation (formulation) of the specific obligation of the members to make additional payments to the company; 2. Consequences of non-fulfillment of the obligation on additional payments and 3. Return of additional payments. Serbian law regarding the regulation of the institute of additional payments contains several inconsistencies and weaknesses that should be de lege ferenda eliminated in order for the application of this type of financing of limited liability companies to be more accepted in domestic business practice.